Self-healing, EMI shielding, and antibacterial properties of recyclable cellulose liquid metal hydrogel sensor. (1st July 2023) - Feng, Xuezhen; Wang, Chao; Shang, Shibin; Liu, He; Huang, Xujuan; Jiang, Jianxin; Song, Zhanqian; Zhang, Haibo
Abstract: Flexible hydrogels are promising materials for the preparation of artificial intelligence electronics and wearable devices. Introducing a rigid conductive material into the hydrogels can improve their electrical conductivities. However, it may have poor interfacial compatibility with the flexible hydrogel matrix. Therefore, we prepared a hydrogel containing flexible and highly ductile liquid metal (LM). The hydrogel can be used as a strain sensor to monitor human motion. The hydrogel showed many properties (i.e., recyclability, EMI shielding properties (33.14 dB), antibacterial (100 %), strain sensitivity (gauge factor = 2.92), and self-healing) that cannot be achieved simultaneously by a single hydrogel. Furthermore, the recycling of LM and their application to hydrogel-based EMI shielding materials have not been investigated previously. Due to its excellent properties, the prepared flexible hydrogel has great potential for applications in artificial intelligence, personal healthcare, and wearable devices. Graphical abstract: Unlabelled Image